A novel combination therapy with Cabozantinib and Honokiol effectively inhibits c-Met-Nrf2-induced renal tumor growth through increased oxidative stress - Laxminarayan Rawat; Murugabaskar Balan; Yuzuru Sasamoto; Akash Sabarwal; Soumitro Pal (Redox Biology, 2023)
Receptor tyrosine kinase (RTK), c-Met, is overexpressed and hyper active in renal cell carcinoma (RCC). Most of the therapeutic agents mediate cancer cell death through increased oxidative stress. Induction of c-Met in renal cancer cells promotes the activation of redox-sensitive transcription factor Nrf2 and cytoprotective heme oxygenase-1 (HO-1), which can mediate therapeutic resistance against oxidative stress. c-Met/RTK inhibitor, Cabozantinib, has been approved for the treatment of advanced RCC. However, acquired drug resistance is a major hurdle in the clinical use of cabozantinib. Honokiol, a naturally occurring phenolic compound, has a great potential to downregulate c-Met-induced pathways. In this study, we found that a novel combination treatment with cabozantinib + Honokiol inhibits the growth of renal cancer cells in a synergistic manner through increased production of reactive oxygen species (ROS); and it significantly facilitates apoptosis-and autophagy-mediated cancer cell death. Activation of c-Met can induce Rubicon (a negative regulator of autophagy) and p62 (an autophagy adaptor protein), which can stabilize Nrf2. By utilizing OncoDB online database, we found a positive correlation among c-Met, Rubicon, p62 and Nrf2 in renal cancer. Interestingly, the combination treatment significantly downregulated Rubicon, p62 and Nrf2 in RCC cells. In a tumor xenograft model, this combination treatment markedly inhibited renal tumor growth in vivo; and it is associated with decreased expression of Rubicon, p62, HO-1 and vessel density in the tumor tissues. Together, cabozantinib + Honokiol combination can significantly inhibit c-Met-induced and Nrf2-mediated anti-oxidant pathway in renal cancer cells to promote increased oxidative stress and tumor cell death.